The diagnostic value of ultrasonography-guided fine needle aspiration biopsy from liver and pancreas - Cansel TÜRKAY; Şahende ELAGÖZ; Özlem YÖNEM; İlhami YÜKSEL and İlhan MURAT (Turkish Journal of Gastroenterology, 2019)
-